Co-planting of Salix interior and Trifolium pratense for phytoremediation of trace elements from wood preservative contaminated soil. Issue 6 (12th May 2021) - Lachapelle, Anne; Yavari, Sara; Pitre, Frédéric E.; Courchesne, François; Brisson, Jacques
Abstract: Phytoextraction potential of a co-planting system was evaluated using a shrub and an herbaceous species and compared with monocultures. A greenhouse experiment with Salix interior and Trifolium pratense grown in combination or alone was conducted for 120 days in soil either uncontaminated or contaminated with wood preservatives containing mixed chromated copper arsenate and pentachlorophenol (PCP). The results showed that the plant species produced similar amounts of dry biomass per pot in monoculture and co-planting, whether growing in contaminated or uncontaminated soil. Arsenic (As), chromium (Cr) and copper (Cu) concentrations in root tissue of S. interior increased 8.6%, 65.9% and 4.5%, respectively, in co-planting compared to its monoculture. T. pratense had superior concentration of As (14% higher) in root tissue when co-planted. However, the higher trace elements concentrations in the plant tissues did not translate into measurable differences in total trace element removal per pot, except for As. The bioconcentration factor for Cu and As was high in the belowground portions of the plants in co-planting. PCP levels in the soil decreased to values near the limit of detection in all treatments. These results suggest that co-planting S. interior with T. pratense could lead to higher phytoextraction potential than monoculture.